Biphasic Equilibrium Dialysis of Poly(N-Isopropyl Acrylamide) Nanogels Synthesized at Decreased Temperatures for Targeted Delivery of Thermosensitive Bioactives - Witold Musial; Jiri Michálek; Janusz Pluta; Anna Jaromin; Magdalena Pietka-Ottlik; Martin Pradny (International Journal of Polymer Science)
Hydrogel nanoparticles, referred to also as nanogels, are of special interest for medical and pharmaceutical applications. Due to small size in the range below the diameter of the capillaries, they are proposed as drug delivery carriers. The aim of the study was to estimate the influence of composition and reaction conditions during synthesis of poly-N-isopropyl acrylamide cross-linked by polyethylene glycol diacrylate on the purification rates of the polymer. Six types of thermosensitive nanogels were prepared by surfactant-free dispersion polymerization and assessed in terms of process yield, composition, and size at temperatures below and over volume phase temperature. During the diffusion of impurities, in the course of dialysis, assessed by the conductometric method, the remarkable influence of temperature and initiator concentration on the process was revealed. The release rates varied in the range between 9.63 · 10−2 and 1.39 · 10−1 h−1 in the first stage of the process, whereas in the second stage they were between 2.09 · 10−2 and 6.28 · 10−2 h−1. The evaluated time to obtain acceptable purity of the preparation was estimated to be in the range of 18 days. More detailed research should be directed towards the influence of the structure of obtained material on the purification process.